Land use, settlement, and plant diversity in Iron Age Northwest France. (April 2018) - van Beek, Roy; Marguerie, Dominique; Burel, Francoise
Various studies using pollen stratigraphies have demonstrated significant correlations between Holocene plant diversity, climate, and human activities. Studies that have analyzed longer Holocene timescales tend to discuss cultural data very superficially. This is remarkable because detailed insights into past human activities may be key to gain an understanding of the observed trends in biodiversity. This study aims to reconstruct and explain spatio-temporal trends in past plant diversity (alpha, temporal, and spatial beta diversity) by integrating data on vegetation dynamics, human subsistence economy, and land-use patterns. The landscape of Northwest France during the greater part of the Iron Age and the start of the Roman period (600 BC–AD 100) is selected as a case study. In total, 30 high-quality pollen-stratigraphical sequences allow for the reconstruction of the main long-term trends in plant diversity and more generally of the changing fabric of the landscape. Additionally, increasingly detailed images of the Iron Age rural landscape are available because of a steep increase in archaeological data (aerial photography, surveys, and excavations). These different types of data are integrated and used as input for a wider discussion on the relation between human activities and plant diversity. In general, the taxonomic richness increases steadily during the period under study. Some spatio-temporal differences are observed. The increasing richness values correspond with the growing impact of human activities on the landscape. Archaeologically documented land-use changes on smaller timescales are less clearly reflected in the richness values and vegetation dynamics, which might result from the (large-scale) research design.